The level of mental and physical depletion of nurses working in neurology departments - Bąk, Jadwiga; Błonka, Ewelina; Borówka, Joanna; Węgorowski, Paweł; Domżał-Drzewicka, Renata (Journal of Education, Health and Sport, 2018)
Introducion. In the nurse profession, contact with another person plays a very important role. In the work environment of nurses there are many factors that are a source of stress, are an increasingly serious problem for working nurses and affect the level of mental and physical exhaustion.Aim. Determination of the level of mental exhaustion and physical exhaustion of nurses working at the Neurology Departments.Material and Methods. The research was conducted among 110 respondents, nurses working at the Neurology Departments in hospitals in the city of Lublin. In the research, the method of the diagnostic survey was used, using the author's questionnaire and the "Japanese Questionnaire".Results. The lowest level of fatigue occurred in people working in an eight-hour one-shift system (p = 0.049). The lowest WCWOZ (the incidence rate of fatigue symptoms) was reported in non-child victims (64.0 ± 65.4). The number of children in family has a statistically significant effect on fatigue (p = 0.034). The vast majority of respondents (86.4%) considered that the nursing staff was insufficient. The number of hours worked per month significantly determined the assessment of the nursing staff (p = 0.007). People employed in Neurology Departments under 5 years rated significantly better chances for promotion (p = 0.012) and had higher ambitions to acquire new professional qualifications (p = 0.00003).Conclusions. Physical and mental exhaustion of working nurses on the examined Neurological Wards is very high. Nurses are much more often tired compared to the surveyed nurses and the younger staff with a much lower WCWOZ. Working in more than one place results in an increase in general fatigueKey words. nurses, work overload, occupational burnout, fatigue